Social Media Users' Interpretations of the Sandra Bland Arrest Video. (October 2019) - Pitman, Brian; Ralph, Asha M.; Camacho, Jocelyn; Monk-Turner, Elizabeth
On July 10, 2015, Sandra Bland, a Black woman, was pulled over by Officer Brian Encinia for failure to signal a lane change in Prairie View, TX. An altercation ensued and Bland was arrested and jailed. Three days later, her body was found in her jail cell and the week following, the dash camera footage was released of her controversial stop and arrest. Utilizing a qualitative content analysis based on a triangulated sample of social media posts in response to the arrest video of Sandra Bland, the current work explores how social media users understand the case of Sandra Bland. Specifically, we focus on where they cast blame and how they explain that blame.